HISTORY AND REPAIR PROCESSES OF THE MOGAKI ATTORI MOSQUE, OR ATTORI MOSQUE HISTORY AND REPAIR PROCESSES - Tursunbayeva Shahlo Bahram's daughter (American Journals, 2024)
In this article, ulmiy research on the study and research of more than 140 architectural monuments, historical architectural monuments erected in Bukhara in the last centuries, the establishment of Khwarezm Samarkand and Bukhara restoration school when the Mughaki attori mosque was restored , as well as the history and repair processes of the Mogagoki Attori mosque, which has kept Bukhara to this day in recognition as a "museum city“, its role in the development of the culture of ours.